PENERAPAN DAN PENGEMBANGAN PADA UMKM MELALUI DIGITAL MARKETING, INOVASI DAN PERHITUNGAN HPP PADA PADA UMKM ARMFOOD - dhameria, vita (Jurnal Penelitian dan Pengabdian Kepada Masyarakat UNSIQ, 2024)
This study aims to determine the obstacles and problems that occur in MSMEs in the city of Cimahi, the selected MSME is ARM Food. MSME ARM Food is engaged in the food sector. The problems that occur in this study are the need for a good marketing strategy, lack of innovation and financial management reports that are still unstructured. While the purpose of this study is to determine the development process in MSMEs using digital marketing ARM food, to determine the strategies that need to be implemented by MSMEs ARM food to follow products that are popular in the market, to determine the calculation of HPP in MSMEs ARM food. The digital marketing application of MSME ARM Food faces challenges in managing social media and has not been optimal in utilizing digital marketing capabilities.